(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2025)
The judgement rules on the unconstitutionality of the reform of the Senate Standing Orders relating to the urgent legislative procedure consisting on the granting of the power to decide whether or not to apply the urgent procedure to private members’ bills to the Senate.